Influence of various chemical treatments on mechanical, thermal and morphological characteristics of Cordia dichotoma fiber - Andoko Andoko; Kuncoro Diharjo; Johny W. Soedarsono; Femiana Gapsari; Sanjay Mavinkere Rangappa; Suchart Siengchin (Case Studies in Chemical and Environmental Engineering)
Understanding the characteristics of Cordia dichotoma fibers (CDf) is essential for optimizing treatment and enhancing performance in composites. This study examines CDf's mechanical, thermal, and morphological properties after treatment with NaOH, NaClO₂, and a combined treatment (NaClO₂ followed by NaOH). NaOH-treated fibers (CDf-NH) exhibited the highest tensile strength (152.8 MPa), crystallinity index (127.57 %), and thermal resistance (up to 380 °C). The combined treatment provided optimal physical and chemical characteristics, enhancing CDf's potential in sustainable composites. These findings support chemical treatments for improving natural fibers in composite applications.